2008
DOI: 10.1603/0046-225x(2008)37[1354:gsosnl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of <I>Sesamia nonagrioides</I> (Lefebvre) Populations in the Mediterranean Area

Abstract: The Mediterranean corn borer, Sesamia nonagrioides (Lefebvre) (Lepidoptera: Noctuidae), is a major pest of maize in the Mediterranean area. Transgenic Bt maize expressing the Cry1Ab toxin from the bacterium Bacillus thuringiensis can effectively control this pest. The characterization of S. nonagrioides population structure, at a large geographical scale, would provide some insight in decision making for resistance management. The genetic relationships among nine populations from Spain, one from France, one fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Our results may be comparable to the ones obtained for other Lepidoptera species, e.g., "Sesamia nonagrioides" in Iran and Spain where subpopulations are separated by larger distances than in the present study. In Iran, genetic differentiation was found between two regions (Southern and Southwestern Iran) separated by 500 km [49], while in Spain, high genetic differentiation was observed between regions separated by distances of 1000 km [50]. AFLP data analysis of individual male and female did not reveal any marker specific for sex determination, and clustering analyses of males and females did not show any particular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may be comparable to the ones obtained for other Lepidoptera species, e.g., "Sesamia nonagrioides" in Iran and Spain where subpopulations are separated by larger distances than in the present study. In Iran, genetic differentiation was found between two regions (Southern and Southwestern Iran) separated by 500 km [49], while in Spain, high genetic differentiation was observed between regions separated by distances of 1000 km [50]. AFLP data analysis of individual male and female did not reveal any marker specific for sex determination, and clustering analyses of males and females did not show any particular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth saying that the sampling areas in southern Europe covered more geographical gradient and range of over 3000 km 2 , whereas in our study, sampling localities in South and Southwest Iran were limited to a distance of 500 km 2 . Previous studies revealed high levels of differentiation among geographically close populations of S. nonagrioides, which could be indicative of the sedentary nature and moderate dispersal behavior of this pest, even when no remarkable geographical barriers exist (De La Poza et al 2008, Cherghali et al 2015. Ecological observations regarding flight behavior and dispersal capacity of S. nonagrioides validate the low dispersal ability of this pest too , Eizaguirre et al 2004).…”
Section: Discussionmentioning
confidence: 88%
“…Pesticides are used by farmers in the case of heavy damage to maize and rice. Management practices of S. nonagrioides in Iran ignore the possible existence of genetic diversity among populations of this pest and its range of distribution.The species S. nonagrioides, is considered one of the most important pests of maize in many countries around the Mediterranean region where it is known as the Mediterranean corn borer or corn stalk borer (De La Poza et al 2008). This pest has been traditionally regarded as a rather sedentary pest , Eizaguirre et al 2004, Margaritopoulos et al 2007), likely to develop genetic isolation between geographical regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Field populations were grouped according to two criteria: 1) by geographical areas, Western Mediterranean (WM) (Spanish and French populations) versus Eastern Mediterranean (EM) (Italian, Greek and Turkish populations), because we found in a previous population genetic study that S. nonagrioides populations from these countries were clustered in these two groups (de la Poza et al 2008); and 2) by history of exposure to Bt plants (Spanish versus the other populations). Mortality values of each area at different concentrations were pooled and analyzed together by probit analysis as described above, to obtain LC 50 and LC 90 values and their 95% Þducial limits.…”
Section: Methodsmentioning
confidence: 99%